Hallmarks of testicular aging: the challenge of anti-inflammatory and antioxidant therapies using natural and/or pharmacological compounds to improve the physiopathological status of the aged male gonad - Matzkin, Maria Eugenia (2021)
The evolutionary theory of aging supports a trade-off relationship between reproduction and aging. Aging of the male reproductive system primarily affects the testes, leading to a decrease in the levels of sexual hormones, alterations in sperm quality and production, and a decline in fertility that does not necessarily involve a complete cessation of spermatogenesis. Inflammation, oxidation, and apoptosis are events considered as predictors of pathogenesis and the development of age-related diseases that are frequently observed in aged testes. Although the molecular mechanisms are still poorly understood, accumulating evidence points toward pro-inflammatory molecules and reactive oxygen species as primary contributing factors for testicular aging. However, the real impact of aging-related testicular alterations on fertility, reproductive health, and life span is far from being fully revealed. This work discusses the current knowledge on the impact of aging in the testis, particularly of aging-related dysregulated inflammation and oxidative damage on the functioning of its different cell populations. More interestingly, this review covers the potential benefits of anti-aging interventions and therapies using either pharmacological compounds (such as non-selective non-steroidal anti-inflammatory medication) or more natural alternatives (such as various nutraceuticals or even probiotics) that exhibit anti-inflammatory, antioxidant, and anti-apoptotic properties. Some of these are currently being investigated or are already in clinical use to delay or prevent testicular aging.